Revision of the genus Philmontis Willemse, 1966 and description of a new genus Philmontoides gen. nov. from New Guinea (Orthoptera: Tettigoniidae; Conocephalinae) - Ingrisch, Sigfrid (Zootaxa, 2022)
The genera Philmontis Willemse, 1966 and Philmontoides gen. nov. are revised. Both genera are of similar general appearance and share a similar color pattern. They differ in the length of the male pronotum that covers the stridulatory area in Philmontis but leaves it free in Philmontoides, by the length of the prosternal spines, by the absence or presence of spines on the inner margin of the hind femur and the hind knees being provided with a single or with two apical spines. The male titillators of Philmontis are often elongate and rather simple, but always terminate into a small sclerotized disc that is missing in Philmontoides and in which the titillators of most species show striking modifications of the apical areas differing among species. The ovipositor is regularly curved to an acute end in Philmontis but has the dorsal valves expanded around mid-length in Philmontoides. The affinity of Nicsara forcipata Willemse, 1966 with the type species of Philmontis (P. nigrofasciatus Willemse, 1966) is confirmed on basis of the homology of the male cerci and titillators in both species. P. minimus Willemse, 1966, originally described as forma of P. nigrofasciatus, is given full species status. Eleven species are described as new in the genus Philmontis Willemse, 1966: Philmontis angustus sp. nov., P. murmur sp. nov., P. banz sp. nov., P. flexus sp. nov., P. extensus sp. nov., P. spinosus sp. nov., P. angulatus sp. nov., P. profusus sp. nov., P. robustus sp. nov., P. pandus sp. nov. and P. pumilus sp. nov.—Lobaspis hageni Dohrn, 1905 is selected as type species of the genus Philmontoides gen. nov. Two species, Nicsara affinis Willemse, 1966 and Philmontis lobatus Naskrecki & Rentz, 2010, are newly combined with Philmontoides. Six species are described as new in that genus: Philmontoides globosus sp. nov., P. disjunctus sp. nov., P. striatus sp. nov., P. geminus sp. nov., P. commodus sp. nov., P. wau sp. nov.